Preschool mental health: The Brief Child and Family Intake and Outcomes System. (March 2021) - Niccols, Alison; Cunningham, Charles; Pettingill, Peter; Bohaychuk, Donna; Duku, Eric
Despite the availability of effective early interventions, few preschoolers with mental health issues receive these services. This situation exists partly due to challenges in the identification of emotional and behavioral issues in young children. We developed the Brief Child and Family Intake and Outcomes System for Preschoolers, which is a 60-item standardized online parent questionnaire including three externalizing scales (Regulating Attention, Impulsivity, and Activity; Cooperating; Regulating Conduct), five internalizing scales (Separating from Parents; Managing Anxiety; Managing Social Anxiety; Regulating Compulsive Behaviour; Managing Mood), and two regulating states scales (Eating; Sleeping). We conducted a normative study of 1, 200 Canadian children 3–5 years old, stratified by sex, age, geographic region, and parents' marital status, income, and education. Confirmatory factor analyses demonstrated good model fit, and the relationship between items and scales did not vary significantly between boys and girls or among 3-, 4-, and 5-year-old children. Reliability estimates indicated high internal consistency and 2-month test–retest reliability for a subsample ( n = 100) ranging from .44 to .73. Providing preliminary evidence of validity, scale scores had positive relations with measures of child functioning challenges, family distress, caregiver mood, and demographic risk variables. We extend earlier work by including clinically relevant emotional-behavioral scales while at the same time minimizing respondent burden and providing norms for Canadian preschoolers. The questionnaire could be used in children's mental health settings, primary care, child welfare, and day-care and school facilities, for intake, triage, and describing 3- to 5-year-old children.